Computer simulation of the indices of the acoustic assessment of machines - D. PLEBAN (Archives of Acoustics, 2014)
Two indices of of the acoustic assessment of machines are proposed: a power index and an emission index which enable the potential user to carry out an acoustic assessment of the machine to be installed in the operation room. The worked out indices are functions of several parameters such as e.g. variations of the operational conditions of the machine, or the acoustic properties of the room. The results of the simulation tests, illustrating the effects of the variation of different parameters on the values of the indices of the acoustic assessment, are given.